2003
DOI: 10.1002/eat.10196
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of bulimia nervosa and eating disorder not otherwise specified is not influenced by personality disorders

Abstract: Objective-To examine prospectively the natural course of bulimia nervosa (BN) and eating disorder not otherwise specified (EDNOS) and to test the effects of personality disorder (PD) comorbidity on the outcomes. Results-Probability of remission at 24 months was 40% for BN and 59% for EDNOS. To test the effects of PD comorbidity on course, ED patients were divided into groups with no, one, and two or more PDs. Cox proportional regression analyses revealed that BN had a longer time to remission than EDNOS (p < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…However, Milos et al 3 found that only 22% of those with AN and 31% of those with BN showed remission over a 2.5-year period. Another study indicated that 40% of the patients with BN recovered over a 2-year follow-up 8 and 74% had recovered by 5-year follow-up. 6 Eddy et al 4 found that 46% of patients with restricting AN and 39% of patients with binge/ purge AN achieved recovery over a period of 8 years.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andmentioning
confidence: 99%
“…However, Milos et al 3 found that only 22% of those with AN and 31% of those with BN showed remission over a 2.5-year period. Another study indicated that 40% of the patients with BN recovered over a 2-year follow-up 8 and 74% had recovered by 5-year follow-up. 6 Eddy et al 4 found that 46% of patients with restricting AN and 39% of patients with binge/ purge AN achieved recovery over a period of 8 years.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andmentioning
confidence: 99%
“…The Collaborative Longitudinal Personality Disorders Study (Gunderson et al, 2000) is a prospective study on the course of four PDs. One report from that study (Grilo et al, 2003) concluded that the natural course of BN and eating disorders not otherwise specified (EDNOS) was not influenced by PDs.…”
Section: Introductionmentioning
confidence: 97%
“…There were no feasible design options to ameliorate this. Recent evidence supports remission of bulimia nervosa in untreated female cases over 24 months (Grilo et al, 2003). However, this study did not find reductions in the bulimia subscale of the EAT-26 over follow-up of between 12 and 24 months in either the treated or treatment as usual group.…”
Section: Study Limitationsmentioning
confidence: 76%
“…Patients with eating disorder and PD have been found to be characterized by chronicity and lower levels of functioning (Skodol et al, 1993) and have poorer outcomes following treatment for their eating disorder than eating-disordered patients without comorbid PD (Johnson, Tobin, & Dennis, 1990;Rossiter, Agras, Telch, & Schneider, 1993). This negative has been shown across a range of treatment approaches, including cognitive behavioural therapy (CBT) (Fahy et al, 1993), pharmacological and combined pharmacological/CBT treatment (Rossiter et al, 1993) and group interpersonal therapy (Wilfley et al, 2000), although the conclusiveness of the evidence for this with respect to bulimia nervosa has been questioned (Bell, 2002;Grilo et al, 2003). It has been recommended that all bulimic patients should be assessed for PD as a matter of routine (Rosenvinge et al, 2000).…”
Section: Introductionmentioning
confidence: 95%